The benefits of flushing with Lemuru fish oil as a source of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) on the performance of reproductive parameters in Garut ewes - Nurlatifah, Aeni; Herdis, Herdis; Khotijah, Lilis; Arifiantini, Iis; ShikhMaidin, Mashitah; Astuti, Dewi Apri; Sitaresmi, Pradita Iustitia; Priyatno, Tri Puji; Lestari, Puji; Santoso, Santoso; Pamungkas, Fitra Aji; Hafid, Anita; et al. (Springer Science and Business Media B.V., 2024)
This study aimed to evaluate and analyze the effects of a flushing diet containing Docosahexaenoic acid (DHA) and Eicosapentaenoic acid (EPA) from Lemuru (Sardinella sp) fish oil on the reproductive performance parameters of Garut ewes. Forty (n = 40) primiparous Garut ewes aged 12–14 months with an average body weight of 28.92 ± 4.94 kg were assigned into four experimental treatment groups. The experimental diets contained roughage: concentrate (30:70%) designated as control concentrate (CNT), flushing concentrate with 6% palm oil (PO), flushing concentrate with 3% palm oil mixed with 3% lemuru oil as DHA and EPA sources (PFO), and flushing concentrate with the addition of 6% lemuru oil (FO). Treatment animals were fed two weeks before and after conception and parturition (8 weeks of total flushing treatment). The addition of fish oil at either 3% (PFO) or 6% (FO) resulted in significantly higher reproductive performance of ewes by increasing the litter size, as reflected by the birth of multiple kids (P < 0.05) compared to CNT and PO. Adding fish oil (PFO and FO) also maintains gestation, resulting in increased lamb yield, especially in the FO treatment, which yields the highest lamb yield (0% single lamb birth). The lamb male ratio was also higher with fish oil supplementation (PFO and PO) (P < 0.05). This research revealed a positive effect of 6% Lemuru oil on decreasing embryo loss and increasing the proportion of twin births. These findings thus support the hypothesis that ration flushing with double the required DHA and EPA from 6% Lemuru fish oil (FO) resulted in significantly higher reproductive performance in Garut sheep.